Tumour calcifications as a prognostic marker in glioblastoma patients treated with bevacizumab - Alexandra Maria Lopes Santos (2022)
Purpose: Glioblastoma (GBM) is the most common and lethal malignant primary brain tumor in adults and its prognosis remains very poor. Bevacizumab (BV) is an anti-angiogenic drug widely used in recurrent GBM. BV can induce GBM calcifications and some authors identified a possible correlation between BV-induced calcifications and better survival. We aim to further investigate the potential role of BV-induced calcifications as a prognostic factor in recurrent GBM. Methods: We did a retrospective cohort study of all patients with GBM between 2007 and 2020 treated at Centro Hospitalar Universitário S. João (CHUSJ) with radiochemotherapy according to Stupp protocol, followed, upon recurrence, by treatment with BV-based therapy. We identified the patients with and without BV-induced calcifications and analysed its impact in progression-free survival (PFS) and overall survival (OS). Results: We included 93 patients. A total of 51.6% developed calcifications after starting a BV-based therapy and the median time of their appearance was 4 months. PFS was significantly different between the group that developed calcifications and the group that did not, with a median PFS of 5 versus 2 months (Log-rank, p = 0.003), respectively. There were no statistically significant differences in OS between groups. Conclusion: BV-induced calcifications are associated with longer PFS in patients with recurrent GBM. While not affecting OS in the group of patients studied, calcifications' appearance might indicate treatment effect and possibly, along with other biomarkers, be useful to assist in the therapeutic decisions.